Faktor-Faktor Yang Mempengaruhi Pengelolaan Keuangan Mahasiswa Akuntansi - Azzahara, Nikken; Samsiah, Siti; Fitriana, Nur (Politeknik Raflesia Press, 2024)
This research to evaluate the financial management of students majoring in accounting at the Faculty of Economics and business, muhammadiyah university or riau. The research method used is quantitative with a likert scale as a measuring tool. The research population consisted of accounting students from the 2019-2022 class, with a total of 473 respondents selected using simple random sampling techniques. Data was collected through distributing questionnaires to accounting students. Data analysis wa carried out using various statistical techniques, including descriptive statistical tests, classical assumption tests, and hypothesis testing using SPSS25. The results showed that the level of financial literacy, family financial education, lifestyle, and financial self-efficacy had a significant effect on management. Acounting student finance. With these findings, it can be concluded that efforts to increase financial literacy, famiy financial education, and financial self-efficacy have a positive effect on the financial management of accounting students at the faculty of Economics and Business, Muhammadiyah University of Riau.